FOREIGN LANGUAGE INCLUSIONS IN MODERN LITERARY TEXT (on the example of English language) (Academicia Globe: Inderscience Research, 2021)
This article deals with one of the urgent problems in modern linguistics, i.e. the functioning of foreign words in the space of a literary text. It is shown that foreign inclusions in a modern literary text possess a high functional status and often take part in the realization of various interpretative techniques.